An Assessment Of Cefiderocol's Synergistic Effects With Eravacycline, Colistin, Meropenem, Levofloxacin, Ceftazidime/Avibactam, And Tobramycin Against Carbapenem-Resistant Pseudomonas Aeruginosa - Bekir Özer; Emel Mataraci Kara; Mesut Yılmaz; Berna Özbek Çelik (Journal of Global Antimicrobial Resistance)
OBJECTIVES: This research examines the combined in vitro effectiveness of cefiderocol with other antibiotics against carbapenem-resistant Pseudomonas aeruginosa (CR-PA) obtained from Intensive Care Units. METHODS: Forty unique CR-PA isolates were evaluated for their minimum inhibitory concentrations (MICs) using broth microdilution. The bactericidal and synergistic effects of cefiderocol, alone or in conjunction with other antimicrobials, were assessed using time-kill curve experiments. RESULTS: Colistin had the lowest MIC50/MIC90 value of 1/2 mg/L, with cefiderocol following at 0.5/4 mg/L against the tested strains. Cefiderocol, levofloxacin, tobramycin, and meropenem showed bactericidal activity against various isolates. Moreover, the most effective synergistic interactions were seen with combinations of cefiderocol and eravacycline, cefiderocol and meropenem, and cefiderocol and ceftazidime/avibactam against the tested strains at 1xMIC concentrations after 24 hours. Antagonism against the analyzed CR-PA strains was not found. CONCLUSION: This study's results indicate that cefiderocol combined with eravacycline, meropenem, or ceftazidime/avibactam showed greater effectiveness against CR-PA bacteria. This dual treatment might be a substitute choice for CR-PA.